Decolonisation Revolution and Evolution - Boucher, David (Wits University Press, 2023)
Multidisciplinary scholars showcase their search for decolonial strategies from within their disciplinary focus, covering ideas such as the different layers at which colonialism operates, strategies for a decolonisation that does not recolonise, and the importance of preserving and publishing in indigenous languages